High P-T Calcite-Aragonite Phase Transitions Under Hydrous and Anhydrous Conditions - Zhao, Xia; Zheng, Zhi; Chen, Jiangzhi; Gao, Yue; Sun, Jianhui; Hou, Xue; Xiong, Mengjun; Mei, Shenghua (Frontiers in Earth Science, 2022)
The subduction of calcite into deep Earth and subsequent phase change are important for global carbon cycle. However, the study of the phase boundary between calcite and aragonite under high P-T conditions is insufficient due to sparse existing phase points and narrow pressure range. In addition, the impact of aqueous fluid on the phase transition requires further investigation. In this work, the calcite-aragonite phase transitions in both anhydrous and hydrous conditions were studied using diamond anvil cell (DAC) with in-situ Raman spectroscopy. In the anhydrous condition, investigations were conducted up to 12 GPa and 400 °C and only the solid recrystallization-reconstructive (SRR) phase transition was observed. The calcite-aragonite boundary shows a convex upward curve with the minimum transformation temperature at around 150 °C and a wide transformation pressure range from 1 to 13 GPa, consistent with the molar volume change between aragonite and calcite-I/II/III/IIIb. In the hydrous condition, both the SRR phase transition and dissolution-precipitation-dehydration (DPD) phase transition were observed under different heating conditions, and in the DPD phase transition ikaite serves as an intermediate phase precipitated from dissolved calcite and then dehydrates into aragonite. Our results suggest the phase transition of calcite-aragonite in the subduction zone, where the SRR phase transition can exist in slabs under wide P-T conditions (1.5 to 2 GPa and 160 to 400 °C), and the DPD process can only occur under lower P-T conditions (less than 1.5 GPa and 110 °C).